Bacteria-Mediated Oncogenesis and the Underlying Molecular Intricacies: What We Know So Far - Prasad, Shashanka K.; Bhat, Smitha; Shashank, Dharini; C. R., Akshatha; R., Sindhu; Rachtanapun, Pornchai; Devegowda, Devananda; Santhekadur, Prasanna K.; Sommano, Sarana Rose (Frontiers in Oncology, 2022)
Cancers are known to have multifactorial etiology. Certain bacteria and viruses are proven carcinogens. Lately, there has been in-depth research investigating carcinogenic capabilities of some bacteria. Reports indicate that chronic inflammation and harmful bacterial metabolites to be strong promoters of neoplasticity. Helicobacter pylori-induced gastric adenocarcinoma is the best illustration of the chronic inflammation paradigm of oncogenesis. Chronic inflammation, which produces excessive reactive oxygen species (ROS) is hypothesized to cause cancerous cell proliferation. Other possible bacteria-dependent mechanisms and virulence factors have also been suspected of playing a vital role in the bacteria-induced-cancer(s). Numerous attempts have been made to explore and establish the possible relationship between the two. With the growing concerns on anti-microbial resistance and over-dependence of mankind on antibiotics to treat bacterial infections, it must be deemed critical to understand and identify carcinogenic bacteria, to establish their role in causing cancer.